Experimental determination of refractive indices in semiconducting films: CDS, TI3O5 - Rodríguez Laura, Sandro (2001)
In this work, we present results of measurements of the refraction index realized withsemiconductors in the form of thin films: cadmium sulfide (CdS) and titan oxide (Ti,O). Theapplied method involves: the determination of the Brewster reflection angle, transmission spectra and optical wave guide effect.